Report of the CNIRD 3rd Regional Biennial Assembly - Dumas, Regina (CNIRD St. AugustineTT, 1992)
Presents a number of papers which address issues relating to the theme of sustainability, focussing specifically on the effects of structural adjustment policies on communities, the need to overhaul the quality of Caribbean life styles and the empowerment of people and communities.